IMPROVING PALLIATIVE CARE ACCESS THROUGH TECHNOLOGY (IMPACTT): PRELIMINARY FINDINGS FROM A PILOT STUDY. (11th November 2018) - Stephens, C; David, D; Wertz, V; Allison, T; Flint, L A; Barrientos, P; Lee, S J; Ritchie, C
Abstract: Nearly 70% of nursing home (NH) residents are eligible for palliative care, yet few receive formal palliative care (PC) outside of hospice in the nursing home setting. We lack a sufficient PC workforce to meet the need in the NH; alternative workforce solutions are needed. We are currently piloting the ImPAcTT intervention in 2 NHs to assess the feasibility and acceptability of study design and procedures, and estimate the impact on symptom distress, advanced care planning, satisfaction, and acute care utilization. 12 residents have been enrolled to date. Baseline data reveals average age 91 (range 83–98), 73% female, 36% Black/African American, 73% widowed, 55% with at least one 30-day readmission. Directors of Nursing stated they would be surprised if 67% of enrolled residents were alive at one year. 83% were perceived to have unrealistic expectations about their health and 100% needed to discuss goals of care.